Preliminary Results About the Use of Argon and Carbon Dioxide in the Extra Virgin Olive Oil (EVOO) Storage to Extend Oil Shelf Life: Chemical and Sensorial Point of View. Issue 9 (12th August 2018) - Sanmartin, Chiara; Venturi, Francesca; Macaluso, Monica; Nari, Anita; Quartacci, Mike F.; Sgherri, Cristina; Flamini, Guido; Taglieri, Isabella; Ascrizzi, Roberta; Andrich, Gianpaolo; Zinnai, Angela
Abstract : The aim of this work is to evaluate the effectiveness of different inert gases, other than nitrogen, to develop a preservation method that can maintain the high quality of extra virgin olive oil (EVOO) increasing its shelf life. The EVOO is stored in the dark at 12 °C in glass containers for about 9 months, and Ar and CO2 are selected as alternative head‐space gases in comparison with air. While the acidity remains constant during the whole observation period, the oxidation‐sensitive parameters show significant differences over time as a function of the gas composition. After only 2 months of storage, the oil stored under air shows a marked decrease of quality, while the use of inert gases slows oxidative degradation and Ar‐treatment best preserves overall oil quality. Compared to samples stored under Ar, at the end of storage the air treatment reduces the phenolic content as well as the antioxidant capacity by 12.0% and 31.3%, respectively, and results in an increase in the peroxide value and K232 of 51.7% and 35.4%, respectively. As CO2 determines a significant negative aftertaste development in oil, it is possible to conclude that this gas cannot be profitably used to optimize EVOO storage conditions. Practical Applications : The identification of an inert gas other than nitrogen able to slow down the oxidative degradation of EVOO both from sensory and chemical points of view, can contribute to identify some possible new strategy to be applied for EVOO long‐term storage at industrial and market level. According to the preliminary results described in this short communication, it should be interesting to better explore the suitability of the total or partial replacement of nitrogen with argon in EVOO storage and packaging. In this context, as the extra‐cost related to food‐grade Ar utilization in comparison with N2 appears close to 17%, the next step of our research will be further investigating also the economic feasibility of the possible combination packaging/storage head‐space atmosphere adopted as a function of specific industrial goal. Experimental conditions adopted to evaluate the effectiveness of different inert gases, other than nitrogen, to develop a preservation method that can maintain the high quality of extra virgin olive oil (EVOO) increasing its shelf life. The EVOO is stored in the dark at 12 °C in glass containers for about 9 months, and Ar and CO2 are selected as alternative head‐space gases in comparison with air. Abstract : Experimental conditions adopted to evaluate the effectiveness of different inert gases, other than nitrogen, to develop a preservation method that can maintain the high quality of extra virgin olive oil (EVOO) increasing its shelf life. The EVOO is stored in the dark at 12 °C in glass containers for about 9 months, and Ar and CO2 are selected as alternative head‐space gases in comparison with air.